2021
DOI: 10.1016/j.ctro.2020.11.016
|View full text |Cite
|
Sign up to set email alerts
|

1.5 T MR-linac planning study to compare two different strategies of rectal boost irradiation

Abstract: Highlights MRI reveals shrinkage of primary tumours during long-course chemoradiotherapy. Intra-fraction motion was assessed by 1.5 T MR-Linac. Adaptive MR-guided boost to GTV with reduced margin revealed better rectum sparing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…With the advent of MRI-Linac hybrid devices it has become possible to considerably reduce planning target volume margins as treatment plans can be adapted to the anatomy of the day based on daily MRI scans. Several studies have shown that planning target volumes required to cover the remaining intrafractional motion with or without rectal filling can be reduced to 4 mm using an online adaptive workflow [2] , [6] , [9] . The present study demonstrates that the addition of rectal ultrasound gel results in more accurate target volume definition in rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the advent of MRI-Linac hybrid devices it has become possible to considerably reduce planning target volume margins as treatment plans can be adapted to the anatomy of the day based on daily MRI scans. Several studies have shown that planning target volumes required to cover the remaining intrafractional motion with or without rectal filling can be reduced to 4 mm using an online adaptive workflow [2] , [6] , [9] . The present study demonstrates that the addition of rectal ultrasound gel results in more accurate target volume definition in rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being able to use the superior soft tissue contrast of the MRI during treatment, the MRI-Linac also allows the treatment plan to be adapted daily to the anatomy of the day. These advantages allow the safety margins for rectal cancer dose escalation to be reduced to a few millimeters instead of 1 cm or more (Bonomo, Lo Russo et al 2021, Eijkelenkamp, Boekhoff et al 2021. At the same time, with such small margins accurate target volume definition becomes more crucial.…”
Section: Introductionmentioning
confidence: 99%
“…The use of MRgRT has raised the quality of all those treatments for which soft tissue visualization is essential, particularly suitable for precision treatments when the targets are close to risky structures and even more when high fractional doses are to be delivered ( 4 , 7 , 9 , 53 , 54 ). MRgRT performed with the Unity Linac allows through the ATS workflow to recalculate and reoptimize the plan using a syCT generated from the daily MRI.…”
Section: Discussionmentioning
confidence: 99%
“…As an interim report and safety analysis, this study has certain limitations. Firstly, with the rapid development of adaptive radiotherapy during the study, the patients who received short-course radiotherapy may bene t more from the MRI-Linac [24], which can provide online treatment MRI images and instruct oncologists to precisely target tumors. Secondly, some patients did not undergo surgery due to cCR, which could cause di culties for the primary endpoint evaluation in the future.…”
Section: Discussionmentioning
confidence: 99%